2012
DOI: 10.1128/aac.01170-12
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity of Isavuconazole against Madurella mycetomatis

Abstract: dCurrently, therapy of black-grain mycetoma caused by Madurella mycetomatis consists of extensive debridement of the infected tissue combined with prolonged antifungal therapy with ketoconazole or itraconazole. In the present study, the in vitro activity of the new triazole isavuconazole toward M. mycetomatis was evaluated. Isavuconazole appeared to have high activity against M. mycetomatis, with MICs ranging from <0.016 to 0.125 g/ml. Due to its favorable pharmacokinetics, isavuconazole could be a promising a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…These MICs were not only considerably lower than those found for ketoconazole and itraconazole in the present study, but they were also lower than those reported for voriconazole (0.016–1 µg/ml), posaconazole (0.03–0.125 µg/ml), and isavuconazole (0.016–0.125 µg/ml) [4], [5], [6]. Only a few reports are available regarding the susceptibility of other eumycetoma causative agents towards ravuconazole.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…These MICs were not only considerably lower than those found for ketoconazole and itraconazole in the present study, but they were also lower than those reported for voriconazole (0.016–1 µg/ml), posaconazole (0.03–0.125 µg/ml), and isavuconazole (0.016–0.125 µg/ml) [4], [5], [6]. Only a few reports are available regarding the susceptibility of other eumycetoma causative agents towards ravuconazole.…”
Section: Discussioncontrasting
confidence: 85%
“…The infection by M. mycetomatis is characterized by the presence of black grains in tissue [3]. Previous reports showed that this fungus was most susceptible to the azole class of antifungal agents [4], [5], [6]. Ketoconazole and itraconazole are the most frequently used drugs for the treatment of mycetoma.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is indicated for the treatment of local and disseminated lesions with or without bone involvement, as it reduces the number of lesions and the duration of drug treatment. Amputation is indicated for cases with massive bone destruction, massive disease that does not respond to prolonged medical treatment and for patients who experience severe drug side-effects (2,15). The use of orthopaedic aids as soon as possible after amputation is essential for achieving a high quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study investigated the in vitro activity of the new triazole antifungal isavuconazole against Madurella mycetomatis . Isavuconazole revealed high in vitro activity against Madurella mycetomatis .…”
Section: Treatment Of Mycetomasmentioning
confidence: 99%